2009
DOI: 10.4049/jimmunol.0901809
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Inflammatory and Proresolving Mediator Resolvin E1 Protects Mice from Bacterial Pneumonia and Acute Lung Injury

Abstract: Whereas pneumonia is the most common cause of death and disability worldwide, most cases of pneumonia spontaneously resolve. Mechanisms that promote pneumonia resolution remain to be determined. Resolvin E1 (RvE1) is an endogenous mediator that displays proresolving actions in sterile inflammation. In this study, we developed a new model of aspiration pneumonia to evaluate the effect of RvE1 on acute lung injury caused by acid aspiration and subsequent bacterial challenge. Mice received hydrochloric acid into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
198
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 199 publications
(205 citation statements)
references
References 56 publications
3
198
1
3
Order By: Relevance
“…49 RvD1 also directly inhibits neutrophil chemotaxis. 21,50 Here, we found that AT-RvD1 dramatically altered the inflammatory environment in cigarette smokeeexposed lungs, with reductions in total inflammatory cells, neutrophils, and the expression of proinflammatory cytokines, Cox-2, and ICAM-1, and increased expression of IL-10. We hypothesize that the reduction in inflammation results from both the direct inhibition of neutrophil chemotaxis and activation as well as inhibition of proinflammatory signaling by epithelial and other lung cells, resulting in decreased levels of expression of chemotactic factors and adhesion molecules.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…49 RvD1 also directly inhibits neutrophil chemotaxis. 21,50 Here, we found that AT-RvD1 dramatically altered the inflammatory environment in cigarette smokeeexposed lungs, with reductions in total inflammatory cells, neutrophils, and the expression of proinflammatory cytokines, Cox-2, and ICAM-1, and increased expression of IL-10. We hypothesize that the reduction in inflammation results from both the direct inhibition of neutrophil chemotaxis and activation as well as inhibition of proinflammatory signaling by epithelial and other lung cells, resulting in decreased levels of expression of chemotactic factors and adhesion molecules.…”
Section: Discussionmentioning
confidence: 61%
“…We and others have reported that RvD1 promotes alternative activation of macrophages (the M2 phenotype) 11,50 and that the M2 macrophages appear to mitigate inflammation and promote the resolution of inflammation in acute models and cell culture systems. 11,51 However, some evidence suggests that in chronic diseases, M2 macrophages may promote tissue remodeling and repair, leading to fibrosis.…”
Section: Discussionmentioning
confidence: 87%
“…19 A total of 1 Â 10 6 colony-forming units of Escherichia coli were introduced to the left mainstem bronchus (total volume, 25 mL). Mice were given ATRvD3 (10 ng, i.v.)…”
Section: E Coli Pneumoniamentioning
confidence: 99%
“…RvE1 diminui a expressão de CD18 em Neutrófilos e Monócitos e modifica a ação da Lselectina (que está relacionada aos eventos iniciais do recrutamento de Leucócitos), resultando na redução da migração de Neutrófilos para o local da inflamação. 2,[54][55][56][57] As resolvinas são produzidas em resposta a um estímulo, têm ação local e têm metabolização por vias enzimáticas que levam à sua inativação. As RvE1 podem ser convertidas a diferentes metabólitos (20-hidroxi-RvE1, 20-carboxi-RvE1, 19-hidroxi-ReV1, 18-oxo-RvE1 e 10, 11-diidro-RvE1) em Neutrófilos humanos que são biologicamente inativos se comparados às RvE1.…”
Section: Resolvinas E Protectinas Resolvinas E Protectinas Resolvinasunclassified
“…As RvE1 podem ser convertidas a diferentes metabólitos (20-hidroxi-RvE1, 20-carboxi-RvE1, 19-hidroxi-ReV1, 18-oxo-RvE1 e 10, 11-diidro-RvE1) em Neutrófilos humanos que são biologicamente inativos se comparados às RvE1. 2,48,[55][56][57] …”
Section: Resolvinas E Protectinas Resolvinas E Protectinas Resolvinasunclassified